Pengaruh Intensitas Bermain Game Online terhadap Konsentrasi Belajar Mahasiswa Program Studi Pendidikan Dokter Umum pada Era Pembelajaran Digital Pascapandemi - Tenriangka, Andi Aulya Puji; Basri, Muh. Iqbal (Institut Agama Islam Negeri (IAIN) Bone, 2025)
This study departs from the phenomenon of increasing internet use in the post-pandemic era of digital learning, where online entertainment activities such as playing online games become an integral part of student life, including medical students. This group is known to have a high academic burden and stress levels, so many of them make online games as a means of fatigue relief or cognitive recreation. However, behind benefits such as improved strategic thinking skills and virtual social interactions, excessive intensity of play can actually decrease the ability to concentrate and focus on learning. In a study that highlights the influence of the intensity of playing online games on the concentration of Student Learning Program of general practitioner education in the era of post-pandemic digital learning, used observational analytical approach with cross-sectional design and data collection through questionnaires regarding the frequency of play and the level of concentration of student learning. The results of the analysis using Spearman's rho test showed a significant negative correlation (p = 0.043; r = -0.233), which means that the higher the intensity of playing online games, the lower the concentration ability of students in academic activities. These findings reinforce the importance of student awareness in managing play time proportionately so that digital entertainment activities do not interfere with the effectiveness of the learning process, especially in medical disciplines that demand high precision, focus, and consistency.. Penelitian ini berangkat dari fenomena meningkatnya penggunaan internet pada era pembelajaran digital pascapandemi, di mana aktivitas hiburan daring seperti bermain game online menjadi bagian yang tak terpisahkan dari kehidupan mahasiswa, termasuk mahasiswa kedokteran. Kelompok ini dikenal memiliki beban akademik dan tingkat stres yang tinggi, sehingga banyak di antara mereka menjadikan game online sebagai sarana pelepas penat atau rekreasi kognitif. Namun, di balik manfaat seperti peningkatan kemampuan berpikir strategis dan interaksi sosial virtual, intensitas bermain yang berlebihan justru dapat menurunkan kemampuan konsentrasi dan fokus belajar. Dalam penelitian yang menyoroti pengaruh intensitas bermain game online terhadap konsentrasi belajar mahasiswa Program Studi Pendidikan Dokter Umum pada era pembelajaran digital pascapandemi ini, digunakan pendekatan analitik observasional dengan desain cross sectional serta pengumpulan data melalui kuesioner mengenai frekuensi bermain dan tingkat konsentrasi belajar mahasiswa. Hasil analisis menggunakan uji Spearman’s rho menunjukkan adanya korelasi negatif yang signifikan (p = 0,043; r = -0,233), yang berarti semakin tinggi intensitas bermain game online, semakin rendah kemampuan konsentrasi mahasiswa dalam kegiatan akademik. Temuan ini memperkuat pentingnya kesadaran mahasiswa dalam mengatur waktu bermain secara proporsional agar aktivitas hiburan digital tidak mengganggu efektivitas proses belajar, khususnya dalam disiplin ilmu kedokteran yang menuntut ketelitian, fokus, dan konsistensi tinggi.